Status Report On Mushroom Based Cosmetic Products In Market - Srivastava, Anuradha; Attri, B L; Sharma, V P (Mushroom Research, 2020)
Mushrooms have been valued as a traditional source of natural bioactive compounds for centuries and have recently been exploited for potential components in the cosmetics industry. Numerous mushrooms and their ingredients have been known to be beneficial to the skin and hair. The representative ingredients are as follows: phenolics, polyphenolics, terpenoids, selenium, polysaccharides, vitamins, and volatile organic compounds. These compounds show excellent antioxidant, anti-aging, anti-wrinkle, skin whitening, and moisturizing effects, which make them ideal candidates for cosmetics products. In the recent times, several types of mushrooms are incorporated in topical creams, lotions, ointments, serums, and facial preparations as cosmetic ingredients. The present article is an effort to provide the status report on various mushroom based cosmetic products available in the markets worldwide.